Names of Dishes and Drinks Derived from Plant Names in Western Polissian Dialect (Linguostylistic Studies, 2019)
The article deals with the investigation of Western Polissian dialect lexical structure which presents a particular interest as far as it concerns lexics reflecting different language changes in local dialect. Western Polissian dialects are the real treasure for Slavic phyilology. The article elucidates the lexical and topical group of the names of dishes and drinks which are ancient and worth of studying in the course of history of language, in particular semantic transformation as a result of metonymical changes based on botany lexics. The study has revealed basic semantic models. Food as a human everyday need reveals most people’s everyday life, their characters and traditions, their nutrition preferences, limitations, and prohibitions, and therefore it is a valuable source for researchers. The relevance of the investigation is due to the lack of a systemic description of the thematic vocabulary group “foodstuff names” in the Western Polissian dialects.The purpose of the article is to describe the names of dishes and drinks that are related to the names of the plants on the material of Western Polissian dialect lexicon. The names of dishes and drinks in the Western Polissian dialect form a rich thematic group of vocabulary, the degree of representation and the nominative variability of which are different.The article analyzes more than 500 West Polissian food and drink names based on the names of the plants. One-word examples demonstrate typical for Ukrainian language ways of dish name formation and relevant semantic changes. The article contains examples of suffix derivatives formed from the names of food products and examples of names derived by lexical-semantic method. The main types of complex names of dishes are mostly two-part phrases. The typical structures are substantive phrases with subordinate words expressed by adjectives, participles, and nouns with prepositions. In most cases subordinate elements regardless of the grammatical form denote necessary ingredients of the dishes and methods of food processing or cooking. The repertoire of names testifies the formal variation of the Western Polissian dialect at the phoneme, accent, and grammar levels. A characteristic feature of the analyzed group of words is a wide range of synonyms for many concepts. As usual several terms are used in one locality or even in the sppeech of one and the same respondent, refering to the same phenomenon. Most names have several phonetic, morphological or accentuated variants.
Keywords: thematic vocabulary group; names of dishes and drinks; Western Polissian dialect; ways of nomination; semantic models; nominative variability; lexical variability; derivation